PERBANDINGAN TINGKAT AKURASI DIGITAL SURFACE MODEL (DSM) HASIL EKSTRAKSI CITRA STEREO CARTOSAT-1 DENGAN CITRA STEREO ALOS PRISM - , FEDHI ASTUTY HARTOYO, Taufik Hery Purwanto, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spatial data is the data containing information about position that can be used as tools for modeling the earth topography. One of the spatial data, called DEM (Digital Elevation Model) is presenting the digital based data which can perform the earth topography in better detail. Now, the making of DEM has been developed from using the stereo imagery remote sensing sources and support the making of DEM efficiently and effectively, without left out the data quality. Data quality is one of important thing in analytical process and as crucial source on making decisions. DEM that show the land cover and topography is defined as Digital Surface Model (DSM). Cartosat-1 stereo images and ALOS prism stereo images are stereo imagery examples that can be used as sources for making DSM. In this research, DSM automatic extractions are executed based on Cartosat-1 stereo images and ALOS prism stereo images, using image matching technique and Rational Polynomial Coefficients (RPC) data. The research purposed is to compare the extraction result between data that taken from the both images, based on both horizontal and vertical accuracy for making 1 :25000 scale map. As a result, at 90% confidence, the horizontal accuracy of DSM Cartosat-1 is 80,2318 meter and 1,6052 meter for vertical accuracy, whereas, the horizontal accuracy of DSM ALOS PRISM is 31,7820 meter and 1,5590 meter for vertical accuracy. Based on those result, the both DSM are not qualified as sources for making 1 :25000 scale map.